Proceso evolutivo de la morfología entre el espacio público y el espacio privado de la Cooperativa Cemento Chimborazo en Riobamba, Ecuador - Bustamante Moreno, Alexis Omar (2023)
The Chimborazo Cement Cooperative, due to its expansion and conservation of the orthogonal checkerboard of a colonial city, has a history of urban planning, changes in land use, stated between the years 1983-2022, affected the urban morphology of sector Z17, reflected in its formal and functional scope, with a variety of existing built typologies. The lack of municipal planning and urban-architectural ordinances subsequent to the initial ones, generated self-planning with self-financing for the consolidation of the project, sorting to the sale and auction of land, subdivisions with variations in property relations, reduction of green area, privatization of the public space, where the change in the use of urban land generated an evolutionary process in urban morphology with different patterns in peri-urban spaces of the City of Riobamba. With planning based on a certain number of population, the difficulties are evident, because it seeks to satisfy new needs, such as population growth, with concepts outside of present and future social reality, within a period of modernity, causing changes in its morphology. This study has the purpose of evaluating the evolutionary process of the morphology between the public space and the private space of the Cemento Chimborazo Cooperative and the changes caused in the historical fact, with the results obtained from the diagnosis it is stated proposal that seeks to improve the functional and formal habitability conditions of the area of study